In-depth comparison of Anc80L65 and AAV9 retinal targeting and characterization of cross-reactivity to multiple AAV serotypes in humans - Maura K. Schwartz; Shibi Likhite; Tatyana A. Vetter; Megan C. Baird; Vicki McGovern; Andrea Sierra Delgado; Tom Mendel; Arthur Burghes; Kathrin C. Meyer (Molecular Therapy: Methods & Clinical Development, 2023)
Anc80L65 is a synthetic, ancestral adeno-associated virus that has high tropism toward retinal photoreceptors after subretinal injection in mice and non-human primates. We characterized, for the first time, the post-intravitreal cell-specific transduction profile of Anc80L65 compared with AAV9. Here we use Anc80L65 and AAV9 to intravitreally deliver a copy of the gene encoding GFP into WT C57Bl/6J mice. GFP expression was driven by one of two clinically relevant promoters, chicken β actin (CB) or truncated MECP2 (P546). After qualitative assessment of relative GFP expression, we found Anc80L65 and AAV9 to have similar transduction profiles. Through the development of a novel method for quantifying GFP-positive retinal cells, we found Anc80L65 to have higher tropism in Müller glia and AAV9 to have higher tropism in horizontal cells. In addition, we found P546 to promote GFP expression at a more moderate level compared with the high levels seen under the CB promoter. Finally, for the first time, we characterized Anc80L65 cross-reactivity in human sera; 83% of patients with AAV2 pre-existing antibodies were found to be seropositive for Anc80L65. This study demonstrates the expanded therapeutic applications of Anc80L65 to treat retinal disease and provides the first insights to Anc80L65 pre-existing immunity in humans.